SOME PROBLEMS OF CONFISCATION OF PROPERTY OF ILLICIT ORIGIN IN THE CONTEXT OF RESTRICTION OF PROPERTY RIGHTS - Hakobyan, Hasmik (State and Law, 2024)
One of the most serious problems facing the legal system in modern times is the detection of illicit income and the implementation of confiscation mechanisms of the property acquired with it. The need to introduce the institution of confiscation of assets without a conviction stems from the considerations of more effective implementation of the fight against corruption. In order to implement this toolkit, the Armenian legal system provided for the implementation of the legal possibility of confiscation of property of illicit origin, the main purpose of which is the confiscation of property not justified by legal income as an effective means of fighting corruption. Meanwhile, in this matter, it is important not only to provide appropriate legislative regulations, but also to guarantee the constitutionality of these regulations. In the context of this report, within the framework of this study, such legal issues as the certainty and clarity of the legal regulations established by the RA Law "On confiscation of property of illicit origin", as well as the issues of interference with the constitutionally guaranteed property rights, were discussed. Within the framework of the study, the need to implement the institution of confiscation of illegally-sourced property as an effective means of combating corruption was highlighted, on the other hand, it was noted the need to implement the possibility of implementing this measure exclusively by taking into account the constitutional principles of legal certainty, prohibition of discrimination and proportionality.
Keywords: corruption; illicit origin; civil forfeiture; forfeiture of property; property rights; legal certainty; exclusion of arbitrariness